Co-Presence Communities: Using Pervasive Computing to Support Weak Social Networks. - Lawrence, J; Payne, T; Roure, D (IEEE, 2006)
Although the strongest social relationships feature most prominently in our lives, we also maintain a multitude of much weaker connections: the distant colleagues that we share a coffee with in the afternoon; the waitress at a our regular sandwich bar; or the 'familiar stranger' we meet each morning on the way to work. These are all examples of weak relationships which have a strong spatial-temporal component but with few support systems available. This paper explores the idea of 'Co-presence Communities' - a probabilistic definition of groups that are regularly collocated together and how they might be used to support weak social networks. An algorithm is presented for mining the Copresence Community definitions from data collected by Bluetooth-enabled mobile phones. Finally, an example application is introduced which utilises these communities for disseminating information. © 2006 IEEE.